Through the vale of darkness history in South Malakula, Vanuatu - de Lannoy, J (2004)
The thesis is a multi-vocal and localized history of the destruction of ancient Malakulan society through depopulation, migration and conversion, of the salvation of some people who gathered around Christian communities, and of the relationship of these people and their descendants to the places they have left and to the communities in which they now live. The thesis brings a historical perspective to Vanuatu anthropology. Compared to earlier work in anthropological history in the Pacific by Sahlins, Dening and Bronwen Douglas, the main innovation in method is that all historical statements are set in their context, emphasizing the multiplicity of view points and revealing the significance of even minor variations which refer to important local issues, from land disputes to conversion to Christianity. Innovative use is made of funerary inscriptions, local maps and court archives, reflecting local forms of historical literacy. The research is part of a growing interest in Christianity in Oceania, after a long neglect by anthropologists. This is the first historical anthropology of Vanuatu and perhaps Melanesia to consider the long-term social impact of the dramatic depopulation that accompanied the colonial expansion of Europeans. The abandonment of the interior of the island of Malakula and the weakening of traditional links with other islands have reduced the social space of Malakula to the original zone of contact with Europeans, the coastal areas and nearby small islands. I argue that Christianity allowed the people of Malakula to create a new form of sociality in response to these events. The new society has its own time and space organized around the nuclear family meal and Sunday service, which were the two cornerstones of the conversion process, symbolizing the abandonment of former ritual activities and of the segregation of cooking fires according to ritual status. This process of cultural adaptation continues with the appropriation by villagers of the historical perspective of official courts favouring material evidence and legalistic principles in land disputes. Earlier research on Vanuatu was dominated by the themes of 'kastom', a discourse on tradition opposed to Western ways, and of the rootedness of people in place. This double emphasis is linked to the fact that most fieldwork in the country was done in the 1970s before a fifteen years ban on foreign research after Independence in 1980. In the context of the struggle for Independence and the restitution of alienated land, Vanuatu people needed to emphasize indigenous values and attachment to land. Today, priorities on the ground have changed and new types of discourses have come to the fore emphasizing conversion to Christianity and adopting new concepts reflecting a shift in preoccupation from recovering colonial land to the relation between indigenous Christian migrants and original owners.